Development of an Integrated Graduate Portal (IGP) for Graduate Marketability - Salako Taofiqat Adebosola
Graduate marketability has become an important issue as many graduates have problem in getting employed after completion of their study in the university.This is as a result of their inability for them to be able to showcase their achievements and market their skills to prospective employers. This thesis firstly identifies the user requirements from all identified stakeholders, and secondly, based on these findings, based on these findings, develops a portal prototype that incorporates the integrated features called the Integrated Graduate Portal (IGP). Finally, the thesis evaluates the use of the IGP in facilitating graduate marketability.The aims of this portal are to facilitate graduate marketability by showcasing graduates contents and skills through the use of electronic portfolio (e-portfolio) to employers and to reduce the communication gap between the employers, graduates and their university.Two phases of survey were conducted for this study.The first one was conducted to identify and gather the user requirements from all adentified stakeholders (graduates, employers, lecturers and administrator). These requirements were analysed and carefully selected before incorporating them during the development of the portal. Once the prototype of IGP was developed, the second survey was conducted to evaluate the use of IGP to facilitate graduate marketability. The evaluation results showed that the IGP may help in facilitating graduate marketability.It was found that integration features such as graduates e-portfolios, employers job requirements information, verification of ga]raduates content by lecturers and collaboration of graduates, employers and university in the IGP are features that may aid graduates in facilitating their marketability. In conclusion, it is hoped that the use of the IGP may help the graduates to facilitate their marketability and bridge the communication gap between the graduates, employers, lecturers and university, therefore improving the interaction and collaboration between all stakeholders.